ANALISIS PEMANFAATAN MEDIA KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK TK KELOMPOK B - Farlina Hardianti; Sry Anita Rachman; Fithrii Muzdalifah (JURNAL ILMIAH GLOBAL EDUCATION, 2022)
This research was aimed to describe the implementation of picture word cards media by teachers at RA Al-Aufiya NW to children of B group. The method of this research was used descriptive research in the form of survey method. This research used data collected technique through non test at RA Al-Aufiya NW using interview, questionnaire, and observation method. The result of this research was analyzed with the steps of Editing, Coding, and Scoring, that describe a picture word cards media in learning activities. The result of this research showed that a picture word cards media is one of the media used by teachers to improve the aspect of children’s language especially the basic skill of reading at Children of B group. However, the used of this media is very rare, because the teachers use media writing and journal more often. A picture word cards can improve the students’ enthusiasm for learning.